Iterative Positive Solutions to Nonlinear $q$-Fractional Differential Equations with Integral Boundary Value Conditions (Journal of Nonlinear Modeling and Analysis, 2024)
This paper is concerned with the existence of positive solutions tononlinear $q$-fractional differential equations yielding to the integral boundaryvalue conditions. Under sufficient conditions of the nonlinearity, by using someiterative techniques, we get that this problem has two positive solutions and aunique positive solution respectively. Our results improve some recent work.
Keywords: Integral boundary value condition; $q$-fractional differential equation; iterative technique; positive solutions.